Fatty Acid Amide Hydrolase Inhibitors - Progress and Potential - K. Khanna, Ish; W. Alexander, Christopher (CNS & Neurological Disorders - Drug Targets, 2011)
Fatty acid amide hydrolase (FAAH) is responsible for hydrolysis of endocannabinoid, anandamide (AEA), and N-acyl ethanolamines such as palmitoylethanolamine (PEA) and N-oleoylethanolamide (OEA). Genetic deletion or pharmacological inactivation of FAAH shows site-specific elevation of AEA that plays a role in the modulation of pain and other neurodegenerative disorders. The review elaborates recent progress and current status of diverse structural classes of reversible and irreversible FAAH inhibitors. The discussion also addresses ligand-enzyme active site interactions and mechanism of enzyme inactivation, emerging approaches to novel FAAH inhibitors, and ongoing efforts to address gaps in therapeutic utility of FAAH inhibitors.
Keywords: Cannabis